The effect of resonance tubes on facial and laryngeal vibration – A case study. (August 2017) - Frič, Marek; Hruška, Viktor
Highlights: Yielding wall model fits better to the experiment than the transmission line model. Resonance tube length and diameter affects the laryngeal vibration maximum frequency. Correlation between EGG and laryngeal displacement is connected with resonance. Abstract: The effects of resonant tubes of different lengths and diameters were measured by means of accelerometers placed on the subject's larynx, forehead and cheek. The electroglottographic (EGG) and acoustical signals were also recorded. The aim of the study was to find the frequency at which the resonance tubes have maximal effect and to find, based on the analysis of the measured signals, the experimental method for the estimation of the resonance frequencies of the elongated vocal tract. The measured data were compared with transmission line modeling (TLM) and the yielding wall model (YWM). Our results show a better fit with the YWM modeled data than with TLM. The experimental data reveal two important kinds of measured maxima which can be identified as the maximum efficiency of the extended vocal tract (the maximum laryngeal vibration) and the correlation coefficient maximum (CCM) between laryngeal vibration and the EGG signal, that we assume to be above the resonance frequency of the extended vocal tract. The vibrational maximum frequency always lies below the CCM and their relative position does not differ by more than 25 Hz.